Social Return on Investment for the University to Tambon Project in Phatthalung Province - Krutchon, Thuanthong (Local Administration Journal, 2024)
The University to Tambon (U2T) project in Phatthalung province has a return on investment of 3.03. For every 1 Thai baht invested in the project, there is a social return or value of 3.03 Thai baht. The SROI analysis of the U2T project in Phatthalung province aims to measure the value or social return on investment that the project generates for the stakeholders. This study is conducted within the framework of the key principles of SROI, which consist of seven main principles: (1) Considering the interests and involvement of stakeholders to maximize their participation, (2) Understanding the changes, (3) Using financial proxies to value major outcomes, (4) Considering only significant aspects, (5) Avoiding overclaiming, (6) Emphasizing transparency at every step, and (7) Being ready for verification. The study applies the theory of change to analyze the inputs, outputs, outcomes, and impacts on all relevant parties, including Tambons, project employees, the private sector, university staff, and government agencies, who play roles in supporting and developing project employees in 62 Tambons in Phatthalung province.